Relationship Between Intelligence, Creativity, Selfesteem and Academic Achievement among Iranian Undergraduate Students in Malaysian Universities - Naderi, Habibollah (2009)
The purpose of this study is to investigate the relationship between intelligence, creativity, self-esteem and academic achievement among Iranian undergraduate students in Malaysian universities. A quantitative research methodology (cross-sectional) was designed for this research. One hundred and fifty three Iranian undergraduates' students were randomly selected out of six universities. Both descriptive and inferential statistics were used to analyze the data in the study using SPSS. The statistical techniques used were Descriptive Statistics, Independent-Sample t-test, Multiple Liner Regression, Chisquare , Multinomial Logistic Regression and Pearson Correlation. The findings in this research study did not support the difference between male and female on creativity. However there was a significant gender difference on the creativity subscales of environmental sensitivity, initiative and what kind of person are you (WKOPAY). Males obtained significantly higher scores on initiative and the WKOPAY subscale than females, but female achieved significantly higher scores on environmental sensitivity than males. The research findings showed that there was no significant difference between female and male students on intelligence. The results of the multiple regression analysis showed that intelligence, gender were not significant predictors of academic achievement. The R2= 0.02 implies that the two predictors variables explain about 0.2 % of the variance in academic achievement. On the other hand, the multiple regression analysis also revealed that creativity, age and gender explained a low proportion (R2= 0.143) of the variation in academic achievement. The findings revealed that the variations in academic achievement explained by the independent variables, intelligence, creativity and gender, was also low. Consequently, a dissimilar aspect of creativity and academic achievement was significant relationship for males and females when looking at the relationships between creativity and academic achievement. The research findings showed that there were significant differences between male and female students on self-esteem. Additionally, the findings of the multinomial logistic regression analysis showed that self-esteem was strong significantly correlated with academic achievement, when gender was controlled. Generally, intelligence, creativity, gender and age were not significant factors in explaining the variance of academic achievement, but self esteem and dissimilar aspect of creativity were the most significant relationship on academic achievement. Implications of the findings are discussed, as well as recommendations for future research. Specially, for students that show characteristics of attribution theory and its causes to which they attribute their success or failure.